Identification of Antioxidant Bioactive Compounds on Leaves of Eggplant Sparrow (Solanum Torvum) From Various Growth Locations - Nunuk Helilusiatiningsih (Publikasi Indonesia, 2022)
Eggplant plants consist of various types such as purple eggplant, index eggplant, sparrow eggplant, Dutch eggplant, and others, easy to grow, and favored by consumers. The aim of the study was to analyze the levels of antioxidant bioactive compounds in the fresh and dried leaves of the sparrow eggplant in various growing locations. The research method is a quantitative chemical test with measurement parameters DPPH, Total Phenol, Tannins, and Flavonoids. Experimental treatments were fresh leaves and dried leaves of sparrow eggplant obtained from 3 locations, namely Malang, Kediri, and Mojokerto. The experimental results showed that there were differences in the content of bioactive compounds in sparrow eggplant leaves at the three locations and the potential of the Batu Malang area with an ambient temperature of around 210 C. - 25 0 C had the highest antioxidant levels, namely wet leaves, and dry leaves in the following order: DPPH 68%, and 70.37%; Total phenol 42.52 mg/g, and 32.13 mg/g; Tannins 0.87 mg/g and 0.76 mg/g; Flavonoids 0.97 mg/g and 2.12 mg/g.